1981
DOI: 10.3109/03790798109167107
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual processes as prerequisites for complex human behaviour

Abstract: Learning implies interaction between the environment and the individual. Thus processing of perceptual information becomes a crucial factor. Perception includes all the mechanisms used in processing the stimuli of an actual situation. Research findings in normal and sensory-deprived children suggest that perceptual development covers the entire period of acquisition of language and other complex human performances. Furthermore, children and brain damaged adults presenting problems of language and other complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…4, is of course only part of the tactile-kinesthetic system which also includes highly integrative functions such as the form recognition specifically tested by Affolter (Affolter and Stricker 1980). Nevertheless, the strong and persistent effects found in the present experiment indicate that fundamental aspects of the tactile-kinesthetic system are af- fected by perinatal MMC exposure.…”
Section: Discussioncontrasting
confidence: 41%
“…4, is of course only part of the tactile-kinesthetic system which also includes highly integrative functions such as the form recognition specifically tested by Affolter (Affolter and Stricker 1980). Nevertheless, the strong and persistent effects found in the present experiment indicate that fundamental aspects of the tactile-kinesthetic system are af- fected by perinatal MMC exposure.…”
Section: Discussioncontrasting
confidence: 41%
“…The primary aim of early rehabilitation after severe TBI was to offer treatment that focused on reducing the extent of the brain injury, preventing complications, and promoting functional recovery through multisensory stimulation performed by an interdisciplinary rehabilitation team integrated in acute care. The early rehabilitation program was based on three different concepts that were originally proposed by Affolter (organization of sensory input) (Affolter, 1981), Bobath (stimulation of normal movement, function and control) (Bobath, 1959) and Coombes (retraining functions of the face and mouth) (Coombes, 2001) which were also called the ABC components. As reported by Kleffelgard and associates (2008), Affolter guiding was the most time-consuming component used for a mean of 45 min per day.…”
Section: Methodsmentioning
confidence: 99%
“…This was supported by Bobath (1978) who also suggested that sensory loss may impair patients' appreciation of size, shape and form, although this was not supported with evidence. Affolter (1981), in a study comparing normal children, sensory deprived children and brain damaged adults, suggested that patients who receive inadequate or distorted sensory information from their environment, fail in everyday tasks. There may be differences between the difficulties experienced by sensory deprived children and adults due to the children experiencing a developmental problem and adults experiencing an acquired problem.…”
Section: Visual Lossmentioning
confidence: 99%